Soil faecal pollution and the risk of hookworm infection in areas of Ibadan, Nigeria (2002)
Soil samples were randomly collected from 25 different observed and suspected human communal defecation locations within Ibadan. All the soil types encountered namely, sand, sandy loam, Sandy, clay loamy, and loamy sand enhanced hookworm larval propagation. The organic matter content showed a decrease with depth. The surface layer soil samples supported hookworm larval growth while the sub soil layer with the same amount of organic matter content as the surface soil layers showed a net zero larval growth. The overall average of 11 x 103 hookworm larvae per gram of soil sample showed a high level of hookworm infestation of the soil. The assessment of food vendor trainee revealed a 36% hookworm infection out of which 80% had low level of awareness of hookworm disease. Furthermore, 75% had no knowledge of transmission of the disease and no evidence of toilet facility was found in their homes. The lack of standard public toilets where they are available at all and lack of knowledge of hookworm disease have contributed to the complexity of the problem of possible spread of hookworm infection in the study area